Discovery of a novel Mediterranean Haemaphysalis (Ornithophysalis) doenitzi group tick species infesting Falco eleonorae on Antikythira Island, Greece - Lidia Chitimia-Dobler; Christos Barboutis; Anastasios Bounas; Christina Kassara; Ben J. Mans; Anastasios Saratsis; Ala Tabor (Parasitology)
Eleonora's falcon (Falco eleonorae Géné, 1839) is a well-known long-distance migrant of the Afro-Palaearctic flyway, a summer breeder of the Mediterranean region and North-west Africa and a winter resident of Madagascar and surrounding areas, thus characterized as a double endemic. Within the context of a long-term monitoring and conservation programme on Antikythira Island, Greece, which accommodates one of the largest concentrations of breeding pairs of Eleonora's falcons globally, birds were subjected to regular inspections for the presence of ticks from 2017 to 2023. In total, 104 adults and 149 nymphs (all belonging to Haemaphysalis genus) were collected. All ticks, apart from 2 nymphs, exhibited broadly salient palpi and did not possess the pronounced palpal segment 2 spurs or spur-like angles that are characteristic of adults, nymphs and most larvae of Rhipistoma, thus placed them in the Ornithophysalis subgenus. Following comprehensive morphological assessment and genetic analysis of the mitochondrial genome by means of next-generation sequencing of both adult and nymphal stages of the ticks, our empirical findings substantiate the delineation of a previously unclassified species. This taxonomic assignment situates the newly described species within the Ornithophysalis subgenus and the Haemaphysalis doenitzi group, marking its presence for the first time within the Western Palaearctic region.